Alarmingly high malnutrition in childhood and its associated factors: A study among children under 5 in Yemen - Al-zangabila, Khaled (Medicine (Baltimore), 2021)
Childhood malnutrition is a serious public health problem in Yemen. However, there is a limited information regarding association of malnutrition with different socio-economic factors. This study examines the correlates of socioeconomic and maternal behavioral factors on malnutrition in Yemeni children under 5 years of age. Our study focuses on the nutritional status of children under 5 years of age, and uses the data provided by the cross-sectional study namely Yemen National Demographic and Health Survey. Three anthropometric indicators: stunting, wasting, and underweight were selected for the evaluation of malnutrition. Independent variables include personal and maternal characteristics, socioeconomic and behavioral factors, and illness conditions. The study used the Chi-Squared test to test the significant association between independent variables and logistic regression to estimate the odds of being malnourished. A total of 13,624 Yemeni children under 5 years of age were included in the study. The results show the high malnutrition level – the prevalence of stunting was 47%, wasting was 16%, and underweight was 39%. There is a statistically significant association between socioeconomic status, behavioral factors, and child malnutrition. The odds of malnutrition decreased with the increase in the level of mother's education, economic status, and frequency of prenatal visits. The odds of malnutrition were least for children whose mothers had highest level of education (OR = 0.64; 95%CI = 0.55–0.76), who belonged to highest wealth index (OR = 0.41; 95%CI = 0.36–0.47). Moreover, the likelihood of malnutrition was less among the children whose mother had highest number of prenatal visits during the pregnancy (OR = 0.67; 95%CI = 0.59–0.76). The high prevalence of stunting, wasting, and undernutrition were found in Yemeni children. Different factors such as regional variations, socio-economic disparities, and maternal education and health care utilization behavior are found to be associated with high malnutrition. These findings provide important policy implications to improving childhood malnutrition in Yemen.